Direct Numerical Simulation of the Pressure Drop through Structured Porous Media - Malico, I. (2015)
Following the development of an immersed boundary method for the study of flow through porous media [1,2], this paper presents direct numerical simulations for structured porous media composed of equal size staggered square cylinders. Different Reynolds numbers are simulated in order to capture the dependence of the pressure drop and friction factor with the Reynolds number. Results are compared to available and widely used empirical correlations. These correlations assume that the additional pressure drop caused by the entrance and exit flow adjustments is unimportant as compared to the pressure drop imposed by the porous medium core. Following this line of though, many of the studies and books on flow though porous media neglect these entrance and exit effects and at best mention them in passing. Through the representation of the pressure drop per unit length for several Reynolds numbers, the authors obtain for a regular matrix composed of equal size square cylinders, the influence of the porous medium entrance. This influence is a function of the Reynolds number.